Nanoarchitectured composite of polysulfone and carbon-based fillers bearing magnetically stimulable function for efficient CO2 capture - Nisar, Muhammad Imran (2024)
Mitigating the global warming caused by CO2 emissions from anthropogenic sources is a hot research topic in the current era. The high cost and difficulty in handling liquid solvent absorbents for CO2 capture are the main barriers to their industrial application. Earth-abundant solid sorbents are favorable candidates for CO2 separation, offering a low energy penalty for CO2 desorption. Here, Polysulfone (PSF) nanocomposites were prepared by simple solution blending. The carbon-based fillers, namely carbon nanotubes (CNT), and activated carbon (CA) in the range of 5–20 wt%, containing iron nanoparticles, were used as fillers. Their morphological, thermal, CO2 capture capacity and magnetic properties were comprehensively studied. Transmission electron microscopy (TEM) evidenced uniform filler distribution in the polymer matrix with sizes of 47–54 nm. Thermal analysis revealed an approximately 4 ◦C improvement in both the initial (Tonset) and maximum (Tmax) degradation temperatures by adding 5 wt% of nanoparticles compared to the pristine polymer. The glass transition temperature (Tg) of the pristine PSF and produced nanocomposites showed identical values as estimated by differential scanning calorimetry (DSC). The increase in filler amount gradually decreased the water contact angle values, indicating a hydrophilic classification of the PSF nanocomposites. The obtained PSF nanocomposites exhibited an efficient CO2 capture capacity of about 40–61 mgCO2/g at 45 ◦C, higher than pristine PSF. This remarkable achievement sets a new benchmark compared to previously developed systems. The introduction of the filler transforms the diamagnetic polymer matrix into a ferromagnet, presenting a coercivity of about 480 Oe, enhancing the material’s potential for applications in microelectronics.